Method for preparing crystalline metal oxide thin film through spontaneous film forming and used device
By mixing the composite mineral particles with acidic metal sulfate -sulfate samples, hydrophilic reactions and oxidation and decomposition have been successfully prepared for metal oxide film with good crystals and high purity, solving the problem of poor crystallization and cost in existing technologies. Realize low -cost and efficient thin film preparation.
Patent Information
- Application Number
- CN202310883933.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, when preparing crystalline metal oxide thin films, the crystallinity is poor, the reaction conditions are high, and the cost is high.
By mixing the composite mineral particles with acidic metal sulfate -sulfate samples, hydrophilic reactions are performed to generate hydrogen -containing hydrogen -containing hydrogel liquid film. The adsorption of heavy metal ions will produce a thin film containing metal hydroxide, and the metal is decomposed through oxidative effects. Oxide.
The prepared crystalline metal oxide film has good crystallinity, high purity, good uniformity, low cost, safe and convenient operation, simple reaction separation device, and low raw material cost.
Smart Images

Figure CN119330309A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal oxide film preparation, and in particular relates to a method for preparing a crystalline metal oxide film by spontaneous film formation and a device used therefor. Background Art
[0002] With the rapid development of modern industry, crystalline metal oxide thin films have broad application potential in many fields as semiconductor materials, dielectric materials, electrode materials, catalysts, sensors, optoelectronic devices, energy storage devices, etc., thus attracting the research interest of many scholars around the world. Therefore, the successful preparation of crystalline metal oxide thin films at low cost has gradually become a hot topic of research at home and abroad. The preparation methods of crystalline metal oxide thin films can be mainly divided into two categories: one is physical methods: evaporation, sputtering, ion plating, etc.; the other is chemical methods: sol-gel method, electrodeposition, hydrothermal method and spray pyrolysis, etc. However, the crystalline metal oxide thin films prepared by the above methods have poor crystallinity, and the above methods have high requirements for reaction conditions. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a method and an apparatus for spontaneously forming a crystalline metal oxide thin film. The crystalline metal oxide thin film prepared by the method provided by the present invention has good crystallinity, high purity, good uniformity, low cost, and safe and convenient operation.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing a crystalline metal oxide thin film by spontaneous film formation, comprising the following steps:
[0006] The composite mineral particles and the acidic heavy metal sulfate water sample are mixed to perform a first hydration reaction, during which the composite mineral particles generate a hydrated gel liquid film containing calcium hydroxide, the hydrated gel liquid film adsorbs heavy metal ions and spontaneously generates a film containing metal hydroxide, the metal hydroxide decomposes to generate metal oxides through oxidation, and thus mineral particles having a crystalline metal oxide film on the outer layer are obtained;
[0007] Separating the crystalline metal oxide film from the mineral particles having the crystalline metal oxide film on the outer layer to obtain the crystalline metal oxide film;
[0008] The method for preparing the composite mineral particles comprises the following steps:
[0009] Mixing bentonite, carbide slag, alkaline activator and water to carry out a second hydration reaction to obtain a second hydration reaction product;
[0010] The second hydration reaction product is sequentially granulated, aged and dehydrated to obtain composite mineral particles;
[0011] The particle sizes of the bentonite and carbide slag are independently ≤74 μm.
[0012] Preferably, the concentration of heavy metal ions in the acidic heavy metal sulfate water sample is 200-1000 mg / L, and the pH value is 3-6; the ratio of the mass of the composite mineral particles to the volume of the acidic heavy metal sulfate water sample is (1-10) g:1L.
[0013] Preferably, when the heavy metal ion concentration in the acidic heavy metal sulfate water sample is 500-1000 mg / L, the temperature of the first hydration reaction is 10-30° C., and the first hydration reaction is performed under static conditions;
[0014] Or when the heavy metal ion concentration in the acidic heavy metal sulfate water sample is 300-500 mg / L, the initial temperature of the first hydration reaction is 10-30° C., when the color of the outer film of the composite mineral particles changes, the temperature is increased to 30-50° C., and the reaction is stopped when the color of the composite mineral particles remains unchanged, and the first hydration reaction is carried out under static conditions;
[0015] Or when the heavy metal ion concentration in the acidic heavy metal sulfate water sample is 200-500 mg / L, the temperature of the first hydration reaction is 10-30°C, the first hydration reaction is initially carried out under static conditions, when the color of the outer film of the composite mineral particles changes, the reaction is carried out under stirring conditions, and the reaction is stopped when the color of the composite mineral particles remains unchanged; the stirring speed is 30-100 r / min.
[0016] Preferably, the alkaline activator comprises sodium carbonate and / or sodium silicate.
[0017] Preferably, the mass ratio of bentonite to carbide slag is (13-36.5):(60-80);
[0018] The mass of the alkaline activator accounts for 3.5-7% of the total mass of the bentonite, carbide slag and the alkaline activator.
[0019] Preferably, the chemical composition of the bentonite includes, by mass percentage: SiO2: 65-80%, Al2O3: 11-17%, Na2O: 3.0-6.0%, CaO: 2.0-3.5%, MgO: 2.0-5.0%, Fe2O3: 1.6-4.0%, TiO2: 0.04-0.20%, K2O: 0.1-1.2%, impurities: 0.10-2.16%;
[0020] The chemical composition of the carbide slag includes: CaO: 86.7-94.5%, SiO2: 2.0-6.5%, Al2O3: 0.5-3.0%, Na2O: 0.5-2.5%, Fe2O3: 0.2-1.5%, MgO: 0.10-0.22%, TiO2: 0.01-0.08%, and impurities: 1.0-1.72%.
[0021] Preferably, the mass ratio of the total mass of the bentonite, carbide slag and alkaline activator to water is 1:(0.6-0.9).
[0022] Preferably, the aging temperature is 10-35° C. and the aging time is 2-12 hours.
[0023] Preferably, the dehydration condensation is: drying under natural conditions for 24 to 48 hours;
[0024] Or the dehydration condensation temperature is 150-450° C., and the time is 0.6-1.5 h.
[0025] The present invention also provides a device for preparing a crystalline metal oxide film using the method described in the above technical solution, comprising a lower plate and an upper plate stacked in sequence; the upper plate is provided with a through hole perpendicular to the lower plate.
[0026] The invention provides a method for preparing a crystalline metal oxide film by spontaneous film formation, comprising the following steps: mixing composite mineral particles and an acidic heavy metal sulfate sample to perform a first hydration reaction, wherein during the first hydration reaction, the composite mineral particles generate a hydrated gel liquid film containing calcium hydroxide, the hydrated gel liquid film adsorbs heavy metal ions to spontaneously generate a film containing metal hydroxide, the metal hydroxide is decomposed by oxidation to generate metal oxide, and mineral particles having a crystalline metal oxide film on the outer layer are obtained; the crystalline metal oxide film in the mineral particles having a crystalline metal oxide film on the outer layer is separated to obtain a crystalline metal oxide film; the preparation method of the composite mineral particles comprises the following steps: mixing bentonite, carbide slag, an alkaline activator and water to perform a second hydration reaction to obtain a second hydration reaction product; the second hydration reaction product is sequentially granulated, aged and dehydrated and condensed to obtain composite mineral particles; the particle sizes of the bentonite and carbide slag are independently ≤74μm.
[0027] The method for preparing a crystalline metal oxide film by spontaneous film formation provided by the present invention comprises adjusting the particle sizes of bentonite and carbide slag, and mixing them with an alkaline activator. Under the action of water, a hydration reaction occurs to form a hydrated calcium silicate (CSH) gel. The composite mineral particles obtained by dehydration condensation are placed in an acidic heavy metal sulfate water sample, absorb water and undergo a hydration reaction to generate a hydrated calcium silicate (CSH) gel again, and release Ca(OH)2 while releasing heat and expanding, so that a temperature difference occurs locally in the same solution around the particles, the composition changes, and an interface layer is formed. The system interface energy tends to be minimized, so the interface is spherical, and due to The slightly soluble Ca(OH)2 has a large local concentration and its solubility is lower at high temperatures, so the Ca(OH)2 colloidal structure forms a skeleton distributed on the spherical interface and a thicker water film is adsorbed on the surface to spontaneously form a colloidal liquid film. The negatively charged colloidal liquid film rich in Ca(OH)2 adsorbs heavy metal cations to generate heavy metal hydroxide precipitation as the initial crystal nucleus to induce crystallization, and generates heavy metal basic sulfate crystals in gel form under acidic conditions. Through the synergistic effect of continuous adsorption-precipitation-crystallization self-growth, a film mainly containing heavy metal basic sulfate crystals is spontaneously generated in the initial stage. As the particles continue to release OH - As the film thickness gradually increases, the OH inside the film - The diffusion rate is reduced, and the OH inside the film - The concentration increases and reacts with the heavy metal alkali sulfate crystals to convert them into heavy metal hydroxides. The heavy metal hydroxides are OH - Under high concentration conditions and high concentration conditions of heavy metal ions, oxidation occurs and gradually transforms into a crystalline metal oxide film, or dissolved oxygen in the water sample contacts the film and induces oxidation, causing the heavy metal hydroxide to gradually transform into a crystalline metal oxide film. The specific reaction is shown in the following formula:
[0028] Ca(OH)2+Cu4SO4(OH)6·2H2O→4Cu(OH)2↓+CaSO4·2H2O
[0029] Cu 2+ +2OH - →Cu(OH)2↓
[0030] Cu(OH)2→CuO+H2O (40℃ alkaline conditions or strong base)
[0031] 2Cu(OH)2+O2→2CuO+2H2O2.
[0032] The present invention separates and recycles a crystalline metal oxide film (the crystalline metal oxide film is mainly composed of metal oxides, and also has a small amount of anhydrous alkaline sulfate such as Cu4SO4(OH)6, and may also contain a small amount of metal hydroxide and a very small amount of CaSO4·2H2O, and does not contain a liquid film of calcium hydroxide) and mineral particles, thereby realizing spontaneous film formation to prepare a crystalline metal oxide film. The results of the embodiments show that the crystalline metal oxide film prepared by the method for spontaneous film formation to prepare a crystalline metal oxide film provided by the present invention has good crystallinity, high purity, and good uniformity, and the reaction and separation device is simple, the raw material cost is low, no substrate or substrate is required, the film can be spontaneously formed, the process flow is short, the operation is safe and convenient, high temperature and high pressure are not required, and energy saving is achieved, and the alkaline industrial solid waste calcium carbide slag can be turned into treasure, waste resource utilization, circular economy, clean production, low-carbon environmental protection and green development can be realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A flow chart of a method for preparing composite mineral particles according to an embodiment of the present invention;
[0034] Figure 2 It is a schematic structural diagram of a device for separating and recovering the crystalline metal oxide film in an embodiment of the present invention;
[0035] Figure 3 Schematic diagram of the film structure formed by the spontaneous formation of colloidal liquid film by hydration reaction of composite mineral particles and adsorption of heavy metal cations as a substrate;
[0036] Figure 4 The composite mineral particles obtained in Example 1 of the present invention spontaneously form a colloidal liquid film and react with the heavy metal Cu in the copper sulfate solution. 2+ The effect diagram of spontaneous film formation to prepare crystalline metal CuO thin film;
[0037] Figure 5 The composite mineral particles obtained in Example 5 of the present invention spontaneously form a colloidal liquid film and react with the heavy metal Zn in the zinc sulfate solution. 2+ The effect diagram of spontaneous film formation to prepare crystalline metal ZnO thin film;
[0038] Figure 6 This is a photograph of bentonite, the raw material of the present invention;
[0039] Figure 7 It is a photo of carbide slag, the raw material of the present invention;
[0040] Figure 8 This is a photograph of the composite mineral particles prepared in Example 1 of the present invention;
[0041] Fig. 9 XRD diffraction patterns of bentonite and carbide slag, the raw materials of the present invention;
[0042] Fig.10 The composite mineral particles obtained in Example 1 of the present invention are 2+ XRD diffraction pattern of crystalline metallic CuO thin film prepared by spontaneous film formation;
[0043] Fig.11 The composite mineral particles obtained in Example 1 of the present invention are 2+ SEM image of crystalline metallic CuO thin film prepared by spontaneous film formation;
[0044] Fig.12 The composite mineral particles obtained in Example 1 of the present invention are 2+ EDS image of crystalline metal CuO thin film prepared by spontaneous film formation;
[0045] Fig.13 The composite mineral particles obtained in Example 2 of the present invention spontaneously form a colloidal liquid film and react with the heavy metal Cu in the copper sulfate solution. 2+ The effect diagram of spontaneous film formation to prepare crystalline metal CuO thin film;
[0046] Fig.14 The composite mineral particles obtained in Example 3 of the present invention spontaneously form a colloidal liquid film and react with the heavy metal Cu in the copper sulfate solution. 2+ The effect diagram of spontaneous film formation to prepare crystalline metal CuO thin film;
[0047] Fig.15 The composite mineral particles obtained in Example 4 of the present invention spontaneously form a colloidal liquid film and react with the heavy metal Cu in the copper sulfate solution. 2+ The effect diagram of spontaneous film formation to prepare crystalline metal CuO thin film;
[0048] Fig.16 The composite mineral particles obtained in Example 4 of the present invention are 2+ SEM image of crystalline metallic CuO thin film prepared by spontaneous film formation;
[0049] Fig.17 This is a diagram showing the effect of the composite mineral particles prepared in comparative example 3 of the present invention in a copper sulfate solution. DETAILED DESCRIPTION
[0050] The present invention provides a method for preparing a crystalline metal oxide thin film by spontaneous film formation, comprising the following steps:
[0051] The composite mineral particles and the acidic heavy metal sulfate water sample are mixed to perform a first hydration reaction, during which the composite mineral particles generate a hydrated gel liquid film containing calcium hydroxide, the hydrated gel liquid film adsorbs heavy metal ions and spontaneously generates a film containing metal hydroxide, the metal hydroxide decomposes to generate metal oxides through oxidation, and thus mineral particles having a crystalline metal oxide film on the outer layer are obtained;
[0052] Separating the crystalline metal oxide film from the mineral particles having the crystalline metal oxide film on the outer layer to obtain the crystalline metal oxide film;
[0053] The method for preparing the composite mineral particles comprises the following steps:
[0054] Mixing bentonite, carbide slag, alkaline activator and water to carry out a second hydration reaction to obtain a second hydration reaction product;
[0055] The second hydration reaction product is sequentially granulated, aged and dehydrated to obtain composite mineral particles;
[0056] The particle sizes of the bentonite and carbide slag are independently ≤74 μm.
[0057] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0058] The present invention mixes composite mineral particles and an acidic heavy metal sulfate water sample, performs a first hydration reaction to generate a hydrated gel liquid film containing calcium hydroxide, the obtained hydrated gel liquid film adsorbs heavy metal ions to spontaneously generate a film containing metal hydroxide, the metal hydroxide decomposes to generate metal oxides through oxidation, and obtains mineral particles with a crystalline metal oxide film on the outer layer.
[0059] In the present invention, the method for preparing the composite mineral particles comprises the following steps:
[0060] Mixing bentonite, carbide slag, alkaline activator and water to carry out a second hydration reaction to obtain a second hydration reaction product;
[0061] The second hydration reaction product is sequentially granulated, aged and dehydrated to obtain composite mineral particles;
[0062] The particle sizes of the bentonite and carbide slag are independently ≤74 μm.
[0063] The invention mixes bentonite, carbide slag, alkaline activator and water to carry out a second hydration reaction, thereby obtaining a second hydration reaction product.
[0064] In the present invention, the chemical composition of the bentonite preferably includes, by mass percentage: SiO2: 65-80%, Al2O3: 11-17%, Na2O: 3.0-6.0%, CaO: 2.0-3.5%, MgO: 2.0-5.0%, Fe2O3: 1.6-4.0%, TiO2: 0.04-0.20%, K2O: 0.1-1.2%, impurities: 0.10-2.16%, more preferably: SiO2: 73.33%, Al2O3: 13.55%, Na2O: 4.25%, CaO: 2.24%, MgO: 3.59%, Fe2O3: 2.26%, TiO2: 0.12%, K2O: 0.50%, impurities: 0.16%. The present invention limits the chemical composition of bentonite to the above range, which is more conducive to the subsequent film formation of composite mineral particles and further fixation and recovery of heavy metal ions.
[0065] In the present invention, the chemical composition of the carbide slag preferably includes, by mass percentage, CaO: 86.7-94.5%, SiO2: 2.0-6.5%, Al2O3: 0.5-3.0%, Na2O: 0.5-2.5%, Fe2O3: 0.2-1.5%, MgO: 0.10-0.22%, TiO2: 0.01-0.08%, impurities: 1.0-1.72%, and more preferably, CaO: 93.65%, SiO2: 2.97%, Al2O3: 0.82%, Na2O: 0.71%, Fe2O3: 0.22%, MgO: 0.15%, TiO2: 0.06%, impurities: 1.42%. The present invention limits the chemical composition of the carbide slag to the above range, which is more conducive to the subsequent film formation of composite mineral particles, and then fixes and recovers heavy metal ions.
[0066] In the present invention, the particle sizes of the bentonite and carbide slag are independently preferably ≤74 μm. The present invention limits the particle sizes of the bentonite and carbide slag to the above range, which can be beneficial to the subsequent hydration reaction, further promote the composite mineral particles to form a colloidal liquid film in acidic wastewater, and spontaneously form a film to prepare a crystalline metal oxide film. If the particle sizes of the bentonite and carbide slag exceed the above range, the prepared composite particles will not be able to spontaneously form a film in acidic wastewater to prepare a crystalline metal oxide film.
[0067] When the particle size of the bentonite and carbide slag is greater than 74 μm, the present invention preferably pre-treats the bentonite and carbide slag respectively; the pre-treating preferably includes drying, grinding and sieving in sequence. The present invention has no special restrictions on the drying, grinding and sieving operations, and the commonly used operations in the field can be used to make the particle size of the bentonite and carbide slag meet ≤74 μm.
[0068] Before mixing bentonite, carbide slag, alkaline activator and water, the present invention preferably dries the bentonite and carbide slag; the drying is preferably carried out in an oven; the drying temperature is preferably 100-110°C, more preferably 105°C; the drying time is preferably 2-4h, more preferably 3h; the drying is preferably carried out until the moisture content of the bentonite and carbide slag is less than 10%. The present invention has no special requirements on the model of the oven, and the oven commonly used in the art can be used. The present invention limits the drying temperature and time to the above range to fully dry the bentonite and carbide slag.
[0069] In the present invention, the mass ratio of bentonite to carbide slag is preferably (13-36.5):(60-80), and more preferably (15-26):(70-80).
[0070] In the present invention, the alkaline activator preferably includes sodium carbonate and / or sodium silicate, more preferably sodium carbonate. When the alkaline activator is sodium carbonate and sodium silicate, the present invention has no special limitation on the ratio of sodium carbonate and sodium silicate, and any ratio can be used.
[0071] In the present invention, the mass of the alkaline activator preferably accounts for 3.5-7% of the total mass of the bentonite, carbide slag and alkaline activator, and more preferably 4-5%.
[0072] In the present invention, the mass ratio of the total mass of the bentonite, carbide slag and alkaline activator to water is preferably 1:(0.6-0.9), more preferably 1:(0.7-0.9).
[0073] In the present invention, the bentonite, carbide slag, alkaline activator and water are preferably mixed by first mixing the bentonite, carbide slag and alkaline activator and then adding water for second mixing. The present invention has no special restrictions on the specific operation of the first mixing, and the bentonite, carbide slag and alkaline activator can be mixed uniformly. The present invention limits the mixing of bentonite, carbide slag and alkaline activator with water to the above order, which can be conducive to the hydration reaction.
[0074] In the present invention, the mixing of the bentonite, carbide slag and alkaline activator is preferably carried out in a mechanical stirrer. The present invention does not specifically limit the type of the mechanical stirrer, and any type well known to those skilled in the art can be used. The present invention does not specifically limit the mixing temperature and time of the bentonite, carbide slag and alkaline activator, and the bentonite, carbide slag and alkaline activator can be uniformly mixed.
[0075] In the present invention, the second mixing is preferably carried out in a mechanical stirrer; the second mixing time is preferably 10 to 20 minutes, more preferably 15 minutes. The present invention does not specifically limit the model of the mechanical stirrer, and any model familiar to those skilled in the art can be used. The present invention can make the hydration reaction more complete through the second mixing.
[0076] In the present invention, the temperature of the second hydration reaction is preferably 10 to 35° C., more preferably 20 to 25° C.; the time of the second hydration reaction is preferably 10 to 20 min, more preferably 15 min.
[0077] The present invention mixes dry bentonite, carbide slag and an activator. CaO and Ca(OH)2 in the dry carbide slag are hydrolyzed to generate Ca(OH)2 after encountering water H2O, and a large amount of heat is released, which is beneficial to the second hydration reaction. Under the action of water, a hydration reaction occurs to form a large amount of hydrated calcium silicate (CSH) gel, which can improve the cohesiveness and mechanical strength of the particles and is beneficial to the subsequent dehydration condensation of the composite particles to form a large amount of amorphous calcium silicate 3CaO·SiO2 or 2CaO·SiO2, thereby facilitating the first hydration reaction with the treated water sample. The specific reaction in the second hydration reaction is shown in the following formula:
[0078] Na2CO3+Ca(OH)2=2NaOH+CaCO3↓
[0079] 2NaOH+SiO2=Na2SiO3+H2O
[0080] Na2SiO3+Ca(OH)2+nH2O=2NaOH+CaSiO3·nH2O(CSH).
[0081] After obtaining the second hydration reaction product, the present invention granulates the second hydration reaction product. In the present invention, the granulation is preferably wet granulation; the particle size of the particles obtained by the granulation is preferably 2 to 7 mm, more preferably 2 to 5 mm; the equipment used for the granulation is preferably a granulation molding machine. The present invention does not specifically limit the setting of the process parameters for granulation, and the parameter settings well known in the art are used to obtain a particle size that meets the requirements. The present invention limits the particle size of the particles obtained by granulation to the above range, which can improve the effect of spontaneous film formation of composite mineral particles to prepare crystalline metal oxide films.
[0082] After the granulation, the present invention ages the granules obtained by the granulation to obtain aged granules.
[0083] In the present invention, the aging temperature is preferably 10 to 35°C, more preferably 20 to 25°C, and the time is preferably 2 to 12 hours, more preferably 8 to 10 hours. The present invention sets the aging temperature within the above range to make the hydration reaction more sufficient. The present invention can form a colloidal liquid film of composite mineral particles in acidic wastewater through the aging process, and spontaneously form a film to prepare a crystalline metal oxide film.
[0084] In the present invention, the granules obtained by granulation are preferably covered with plastic cloth during the aging process. The present invention can avoid water loss during the aging process by covering, and ensure the amount of water required for the hydration reaction.
[0085] After obtaining the aged particles, the present invention performs dehydration condensation on the aged particles to obtain composite mineral particles.
[0086] In the present invention, the dehydration condensation is preferably dried under natural conditions for 24 to 48 hours, more preferably for 36 to 48 hours;
[0087] Or the dehydration condensation temperature is preferably 150-450°C, more preferably 220-350°C, and the time is preferably 0.6-1.5h, more preferably 1h.
[0088] The present invention sets the temperature and time of dehydration condensation within the above range, so that the composite mineral particles can be fully dried and dehydrated, which is conducive to the subsequent spontaneous film formation of heavy metal ions in acidic wastewater to prepare a crystalline metal oxide film. The present invention can make the composite mineral particles undergo a hydration reaction in acidic wastewater to form a colloidal liquid film through dehydration condensation, and spontaneously form a film to prepare a crystalline metal oxide film.
[0089] When the temperature of the dehydration condensation is 150-450°C, the product obtained by the dehydration condensation is preferably subjected to a cooling treatment; the cooling treatment is preferably natural cooling. The cooling treatment of the present invention can facilitate the preservation of the composite mineral particles.
[0090] Figure 1 The following is a flow chart of the method for preparing composite mineral particles according to an embodiment of the present invention. Figure 1 As shown, the present invention sequentially dries, grinds, sieves and bakes bentonite and carbide slag, then weighs, stirs and mixes them with an alkaline activator (sodium carbonate and / or sodium silicate) in proportion, then adds water in proportion, stirs evenly, and causes a hydration reaction, then sequentially granulates, covers with plastic cloth to keep moisture, ages, naturally dries or bakes, and finally naturally cools to obtain composite mineral particles.
[0091] In the present invention, the pH value of the acidic heavy metal sulfate water sample is preferably 3-6, more preferably 4-5, and the heavy metal ion concentration is preferably 200-1000 mg / L, more preferably 250-500 mg / L; the type of heavy metal preferably includes copper and / or zinc, more preferably copper.
[0092] In the present invention, the ratio of the mass of the composite mineral particles to the volume of the acidic heavy metal sulfate water sample is preferably (1-10) g:1 L, and more preferably (2-5) g:1 L. The present invention limits the usage ratio of the composite mineral particles to the acidic heavy metal sulfate water sample to the above range, so that the heavy metal ions in the water sample can be spontaneously film-formed to prepare a crystalline metal oxide film.
[0093] In the present invention, the first hydration reaction is that when the composite mineral particles are mixed with the water sample, they absorb water to undergo a hydration reaction to generate a hydrated calcium silicate (CSH) gel, and release Ca(OH)2 while releasing heat to expand, so that a temperature difference and composition change occur locally in the same solution around the particles to form an interface layer. The system interface energy tends to shrink to a minimum, so the interface is spherical. Moreover, since the local concentration of the slightly soluble Ca(OH)2 is large and its solubility is lower at high temperatures, the generated Ca(OH)2 colloidal structure forms a skeleton distributed on the spherical interface and a thicker water film is adsorbed on the surface to form a negatively charged colloidal liquid film rich in Ca(OH)2.
[0094] In the present invention, the heavy metal ion concentration in the acidic heavy metal sulfate water sample is preferably 500-1000 mg / L, the temperature of the first hydration reaction is preferably 10-30° C., and the first hydration reaction is preferably carried out under static conditions;
[0095] Or when the heavy metal ion concentration in the acidic heavy metal sulfate sample is preferably 300-500 mg / L, the initial temperature of the first hydration reaction is preferably 10-30° C., when the color of the outer film of the composite mineral particles changes, the temperature is increased to 30-50° C., and the reaction is stopped when the color of the outer film of the composite mineral particles remains unchanged, and the first hydration reaction is preferably carried out under static conditions;
[0096] Or when the heavy metal ion concentration in the acidic heavy metal sulfate water sample is preferably 200-500 mg / L, the temperature of the first hydration reaction is preferably 10-30°C, the first hydration reaction is initially carried out under static conditions, when the color of the outer film of the composite mineral particles changes, the reaction is carried out under stirring conditions, and the reaction is stopped when the color of the outer film of the composite mineral particles remains unchanged; the stirring speed is preferably 30-100 r / min.
[0097] When the heavy metal in the acidic heavy metal sulfate sample is Cu, the reaction is stopped when the color of the outer film of the composite mineral particles changes, preferably when the color of the outer film of the composite mineral particles turns blue-green; the reaction is stopped when the color of the outer film of the composite mineral particles remains fixed, preferably when the color of the outer film of the composite mineral particles turns black.
[0098] When the heavy metal in the acidic heavy metal sulfate sample is Zn, the reaction is stopped when the color of the outer film of the composite mineral particles changes, preferably when the color of the outer film of the composite mineral particles turns white; the reaction is stopped when the color of the outer film of the composite mineral particles remains fixed, preferably when the color of the outer film of the composite mineral particles turns white and transparent.
[0099] The first hydration reaction under the initial static condition can be beneficial to the formation of colloidal liquid film under stable conditions, and is conducive to the self-growth of crystals on the surface of the colloidal liquid film to form heavy metal basic sulfate crystals first. Under static conditions with high concentration of heavy metal ions, the amount of heavy metal basic sulfate crystals generated is large, the film thickness increases rapidly, and the OH inside the film is - The outward diffusion rate decreases rapidly, and the OH inside the film - Higher concentrations mean that heavy metal hydroxides are more likely to form and react with OH - Under high concentration conditions, it gradually transforms into a crystalline metal oxide film; or under the condition of standing still and the water temperature rising to 30-50°C in the middle and late stages, the heavy metal basic sulfate crystals generated in the early stage are prone to have a high concentration of OH in the film. - Under the condition of generating heavy metal hydroxides, and when the water sample is heated to 30-50℃, oxidation occurs and gradually transforms into a crystalline metal oxide film; or when the initial static state and the stirring speed in the middle and late stages are controlled at 30-100r / min, the dissolved oxygen in the water sample is accelerated to contact with the film to cause oxidant-induced oxidation, so that the generated heavy metal hydroxides are gradually transformed into a crystalline metal oxide film. And it is convenient for the separation and recovery of particles and crystalline metal oxide films after subsequent reactions.
[0100] In the present invention, the temperature raising method is preferably heating, and the water temperature can be controlled at 30-50°C in the middle and late stages. The present invention has no special limitation on the heating device, and the heating device commonly used in the art can be used. The present invention limits the temperature of the water sample in the middle and late stages to the above range so that the heavy metal hydroxide converted from the heavy metal basic sulfate crystal film can be better oxidized into a crystalline metal oxide film.
[0101] In the present invention, the stirring is preferably carried out in a shaking table, and the shaking table speed can be controlled at 30 to 100 r / min in the middle and late stages. The present invention has no special limitation on the shaking table equipment, and the shaking table equipment commonly used in the art can be used. The present invention limits the shaking table speed of the water sample in the middle and late stages to the above range so that the heavy metal hydroxide converted from the heavy metal basic sulfate crystal film can be better oxidized to a crystalline metal oxide film by contacting oxygen.
[0102] In the present invention, the adsorption process is preferably that the composite mineral particles and the acidic heavy metal sulfate sample are subjected to the first hydration reaction to generate a negatively charged colloidal liquid film rich in Ca(OH)2 to adsorb heavy metal cations to generate heavy metal hydroxide precipitation, the hydroxide precipitation acts as the initial crystal nucleus to induce crystallization, and generates heavy metal basic sulfate crystals under acidic conditions, and continues to adsorb-precipitate-crystallize heavy metal ions to grow synergistically, first forming a film of heavy metal basic sulfate crystals and then continuing to convert into heavy metal hydroxide and being oxidized to a crystalline metal oxide film to achieve maximum performance. The present invention realizes spontaneous film formation to prepare a crystalline metal oxide film through the synergistic effect of adsorption-precipitation-nucleation-induced crystallization self-growth-oxidation.
[0103] In the present invention, there is a distance between the crystalline metal oxide film and the mineral particles in the mineral particles with the crystalline metal oxide film on the outer layer. When the composite mineral particles are mixed with wastewater, they absorb water to generate hydration reaction to generate hydrated calcium silicate (CSH) gel, and release Ca(OH)2 while releasing heat to expand, so that the same solution around the particles has a local temperature difference and composition change to form an interface layer, which continuously expands outward to form a certain distance with the particles, and the system interface energy tends to shrink to the minimum, so the interface is spherical, and because the local concentration of slightly soluble Ca(OH)2 is large, the solubility is lower at high temperature, and the generated Ca(OH)2 colloidal structure forms a skeleton distributed on the spherical interface and adsorbs a thicker water film on the surface to form a negatively charged colloidal liquid film rich in Ca(OH)2, that is, there is a distance between the colloidal liquid film and the mineral particles, and the crystalline metal oxide film finally formed has a distance between the mineral particles.
[0104] After obtaining the mineral particles having a crystalline metal oxide film on the outer layer, the present invention separates the crystalline metal oxide film in the mineral particles having a crystalline metal oxide film on the outer layer to obtain the crystalline metal oxide film and the mineral particles respectively.
[0105] In the present invention, the mineral particles are preferably mineral particles with a loose porous structure formed by releasing Ca(OH)2 from composite mineral particles through a first hydration reaction.
[0106] In the present invention, the separation is preferably mechanical peeling.
[0107] In the present invention, the crystalline metal oxide film is preferably recycled as a raw material or finished product, and more preferably as a raw material or finished product of a semiconductor material, a dielectric material, an electrode material, a catalyst, a sensor, an optoelectronic device, an energy storage material, and a heavy metal oxide. In the present invention, the mineral particles are preferably dried and recycled as an adsorbent, and more preferably used to adsorb heavy metal ions in low-concentration heavy metal acidic wastewater. In the present invention, the heavy metal ions in the low-concentration heavy metal acidic wastewater are preferably Fe 2+ , Mn 2+ , Cu 2+ 、Zn 2+ , Hg 2+ 、Cd 2+ , Pb 2+ Cr 3+ and Ni 2+ One or more of the above; the concentration of heavy metal ions in the low-concentration heavy metal acidic wastewater is preferably 0.1-50 mg / L, more preferably 5-40 mg / L. The present invention can realize low-cost, simple process, spontaneous film formation preparation of crystalline metal oxide film by separately recovering crystalline metal oxide film and mineral particles, and can realize the transformation of alkaline industrial solid waste calcium carbide slag into treasure, waste resource utilization, circular economy, low carbon, green, and environmental protection.
[0108] In the present invention, when the mineral particles are used as adsorbents to adsorb heavy metal ions in low-concentration heavy metal acidic wastewater to saturation, the present invention preferably dries the saturated adsorbent and recovers it as a metal mineral resource.
[0109] In the present invention, the drying is preferably carried out under natural conditions for 24 to 48 hours or at high temperature; the high temperature drying is preferably carried out in an oven; the temperature of the high temperature drying is preferably 105°C, and the time of the high temperature drying is preferably 2 to 4 hours. The present invention does not specifically limit the model of the oven, and an oven commonly used in the art can be used. The present invention limits the drying temperature and time to the above range so that the recovered composite mineral particles can be fully dried. The present invention utilizes the characteristics of the particles obtained after the hydration reaction, that is, the porosity becomes larger and the specific surface area increases, which is more conducive to being used as an adsorbent and is easy to recycle, has no waste discharge, is green and environmentally friendly, and can achieve a circular economy.
[0110] The method for the fixed separation and recovery of heavy metal ions by film-forming mineralization provided by the present invention comprises the following steps: adjusting the particle sizes of bentonite and carbide slag, mixing them with an alkaline activator, causing a hydration reaction under the action of water to form a hydrated calcium silicate (CSH) gel, etc., thereby improving the cohesiveness and mechanical strength of the particles; aging the particles obtained after the hydration reaction and granulation to make the hydration reaction in the particles more complete, and drying the water in the hydrated calcium silicate (CSH) gel by dehydration condensation to condense the particles; when the composite particles after dehydration condensation are used, they are placed in water to absorb water, undergo a hydration reaction, and generate a hydrated calcium silicate (CSH) gel again, and release Ca(OH)2 simultaneously releases heat and expands, causing a temperature difference and composition change in the wastewater around the particles to form a spherical interface layer rich in Ca(OH)2 colloidal structure, and adsorbs a thicker water film to form the initial colloidal liquid film. The negatively charged colloidal liquid film rich in Ca(OH)2 adsorbs heavy metal cations to form metal hydroxide precipitation, which acts as an initial nucleation-induced crystallization and forms heavy metal basic sulfate crystals under acidic conditions. Through the continuous adsorption-precipitation-crystallization self-growth synergistic effect, a film of heavy metal basic sulfate crystals is first formed and then further converted into heavy metal hydroxide and oxidized into a crystalline metal oxide film. By separating the crystalline metal oxide film from the particles, the spontaneous film formation of heavy metal ions to prepare a crystalline metal oxide film is achieved.
[0111] The present invention also provides a device used in the method described in the above technical solution, comprising a lower plate and an upper plate stacked in sequence; the upper plate is provided with a through hole perpendicular to the lower plate.
[0112] In the present invention, the upper plate is provided with a through hole perpendicular to the lower plate; the diameter of the through hole is preferably 2 to 3 mm larger than the length of the composite mineral particles, the center distance of the through hole is preferably 2 to 4 times the diameter of the through hole, and the depth of the through hole is preferably 1 to 2 mm. The present invention limits the through hole parameters on the upper plate to the above range, which can be more conducive to the growth of the crystalline metal oxide film on the upper plate and more convenient for the subsequent separation and recovery of the mineral particles and the crystalline metal oxide film.
[0113] The present invention preferably sets a vertical card plate on the lower plate, and the length of the vertical card plate is preferably 5 cm, the width is preferably 1 cm, and the height is preferably 5 mm greater than the sum of the thickness of the upper plate and the lower plate. The present invention has no special requirements for the number of vertical card plates set on the lower plate, and can ensure that the upper plate and the lower plate are firmly fixed during use, and ensure that the upper plate and the lower plate do not slide. The present invention sets a vertical card plate on the lower plate to fix the upper plate and the lower plate, ensuring that the upper plate and the lower plate do not slide during the spontaneous film formation of heavy metal ions to prepare a crystalline metal oxide film, which is conducive to the formation of a crystalline metal oxide film on the outer layer of the composite mineral particles.
[0114] The present invention sets the vertical card plate in the above-mentioned connection mode, so that the upper plate and the lower plate can be fixed during the process of spontaneous film formation of heavy metal ions to prepare crystalline metal oxide thin films, avoiding sliding of the upper plate and the lower plate, which is more conducive to the growth of crystalline metal oxide thin films. After the process of spontaneous film formation of heavy metal ions to prepare crystalline metal oxide thin films is completed, it can be beneficial to separate the upper plate from the lower plate, which is beneficial to the separation and recovery of composite mineral particles and crystalline metal oxide thin films.
[0115] In the present invention, the materials of the upper plate, the lower plate and the vertical cardboard are independently preferably organic plastic templates. The present invention can avoid corrosion of the device in acidic wastewater by setting the upper plate, the lower plate and the vertical cardboard to the above materials.
[0116] In the present invention, the method of using the device is preferably: after mixing the composite mineral particles and the acidic heavy metal sulfate sample, place them in the device, perform a first hydration reaction, discharge the acidic heavy metal sulfate sample after the first hydration reaction and recycle them multiple times, and take out the upper plate with the crystalline metal oxide film grown, the crystalline metal oxide film remains on the upper plate, and the mineral particles remain on the lower plate, completing the separation of the crystalline metal oxide film and the mineral particles, and then gently scrape the crystalline metal oxide film on the upper plate to make it fall off and collect and recycle, and collect and dry the mineral particles left on the lower plate as by-products. The present invention can better separate the prepared crystalline metal oxide film from the mineral particles through the device, so that the crystalline metal oxide film and the mineral particles can be recycled separately.
[0117] Figure 2 FIG. 1 is a schematic diagram of the structure of the device for separating and recovering the crystalline metal oxide film in an embodiment of the present invention. Figure 2 As shown, the device for separating and recovering the crystalline metal oxide film comprises a lower plate, an upper plate and a vertical card plate for fixing the lower plate and the upper plate. Figure 2The separation and recovery device for preparing crystalline metal oxide thin films by spontaneous film formation of heavy metal ions shown can better separate particles with crystalline metal oxide thin films on the outer layer, and can improve the separation and recovery efficiency and recovery rate of the prepared crystalline metal oxide thin films.
[0118] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0119] Example 1
[0120] A heavy metal Cu 2+ The method for preparing a crystalline metal CuO thin film by spontaneous film formation comprises the following steps:
[0121] 1.0 g of composite mineral particles were evenly dispersed in a device for spontaneous film formation to prepare crystalline metal oxide thin films, and the device was placed in a 1 L liquid with an initial pH of 3.2 and heavy metal Cu 2+ In an acidic heavy metal copper sulfate water sample with a concentration of 300 mg / L, the static conditions and the initial water temperature of the water sample were controlled at 20°C. When the outer film color of the composite mineral particles turned blue-green, the water temperature was raised to 50°C for the first hydration reaction until the outer film color of the composite mineral particles turned black and the reaction was stopped. The initial reaction obtained a colloidal liquid film, and then the heavy metal ion Cu 2+ The synergistic effect of adsorption-precipitation-crystallization self-growth-oxidation is performed to obtain particles having a crystalline metal CuO film on the outer layer; in the particles having a crystalline metal CuO film on the outer layer, there is a distance between the crystalline metal CuO film and the particles;
[0122] The preparation method of the composite mineral particles comprises the following steps:
[0123] The bentonite and carbide slag are dried in an oven at 105°C for 3 hours until the moisture content is less than 10%, and then mixed evenly with sodium carbonate in a mechanical stirrer, and then water is added and mixed for 15 minutes for a second hydration reaction, and then a granulator is used to make particles with a diameter of 2 mm and a length of 3 mm. The granulated particles are covered with plastic cloth, aged at 25°C for 6 hours, and then calcined at 400°C for 1 hour for dehydration condensation, and then naturally cooled to obtain composite mineral particles; the particle size of the bentonite and carbide slag is independently ≤74μm; the mass ratio of the bentonite and carbide slag is 25.5:70; the mass of the sodium carbonate accounts for 4.5% of the total mass of the bentonite, carbide slag and sodium carbonate; the bentonite, carbide slag and carbon are 1.34 μm and 1.34 μm, respectively. The mass ratio of the total mass of sodium phosphate to water is 1:0.8; the chemical composition of the bentonite is as follows by mass percentage: CaO: 2.24%, SiO2: 73.33%, Al2O3: 13.55%, Na2O: 4.25%, Fe2O3: 2.26%, MgO: 3.59%, TiO2: 0.12%, K2O: 0.50%, impurities: 0.16%; the chemical composition of carbide slag is as follows by mass percentage: CaO: 93.65%, SiO2: 2.97%, Al2O3: 0.82%, Na2O: 0.71%, Fe2O3: 0.22%, MgO: 0.15%, TiO2: 0.06%, impurities: 1.42%;
[0124] The heavy metal Cu 2+ A device for preparing a crystalline metal CuO thin film by spontaneous film formation comprises a lower plate and an upper plate which are stacked in sequence; the upper plate is provided with a through hole; the lower plate is provided with a vertical card plate, and the upper plate and the lower plate are fixed together by the vertical card plate; the through hole of the upper plate has a diameter of 5 mm and a depth of 1 mm, the diameter of the through hole is 2 mm larger than the length of the composite mineral particle, and the center distance of the hole is 4 times the diameter of the hole; the length of the vertical card plate is 5 cm, the width is 1 cm, and the height is 5 mm larger than the sum of the thickness of the upper plate and the lower plate;
[0125] After obtaining the mineral particles with a crystalline metal CuO film on the outer layer, the acidic heavy metal copper sulfate water sample after the reaction is discharged and recycled, and the upper plate with the crystalline metal CuO film grown is taken out, the crystalline metal CuO film remains on the upper plate, and the mineral particles remain on the lower plate, completing the separation of the crystalline metal CuO film and the mineral particles, and then the crystalline metal CuO film on the upper plate is gently scraped off to make it fall off and collected for recycling, and the mineral particles left on the lower plate are collected as by-products, naturally dried for 48 hours and then recycled, and the recycled mineral particles can be recycled as an adsorbent for adsorbing heavy metal ions, and the recycled mineral particles can continue to be recycled as metal mineral resources after being saturated with heavy metal ions, thereby realizing a waste-free, green and circular economy.
[0126] The heavy metal Cu provided by the present invention 2+ The crystalline metal CuO film prepared by spontaneous film formation is dark black in color and has a crystal purity of more than 90%. 2+ Spontaneous film formation has a good effect on the preparation of crystalline metal CuO thin films.
[0127] Example 2
[0128] A heavy metal Cu 2+ The method for preparing a crystalline metal CuO thin film by spontaneous film formation comprises the following steps:
[0129] 2.0 g of composite mineral particles were evenly dispersed in a device for spontaneous film formation to prepare crystalline metal oxide thin films, and the device was placed in a 1 L solution with an initial pH of 3.0 and heavy metal Cu 2+ In the acidic heavy metal copper sulfate water sample with a concentration of 300 mg / L, the water sample was controlled at 25°C and initially allowed to stand. When the outer film color of the composite mineral particles turned blue-green, the shaking table speed was set at 100 r / min for the first hydration reaction until the outer film color of the composite mineral particles turned black and the reaction was stopped. The initial reaction obtained a colloidal liquid film, and then the heavy metal ion Cu 2+ The synergistic effect of adsorption-precipitation-crystallization self-growth-oxidation is performed to obtain particles having a crystalline metal CuO film on the outer layer; in the particles having a crystalline metal CuO film on the outer layer, there is a distance between the crystalline metal CuO film and the particles;
[0130] The preparation method of the composite mineral particles comprises the following steps:
[0131] The bentonite and carbide slag are dried in an oven at 105°C for 3 hours until the moisture content is less than 10%, and then mixed with sodium silicate in a mechanical stirrer. Water is then added and mixed for 15 minutes for a second hydration reaction. Then, a granulator is used to make particles with a diameter of 2 mm and a length of 3 mm. The particles obtained by granulation are covered with plastic cloth, aged at 20°C for 10 hours, and then calcined at 220°C for 1 hour for dehydration condensation, and then naturally cooled to obtain composite mineral particles; the particle sizes of the bentonite and carbide slag are independently ≤74μm; the mass ratio of the bentonite and carbide slag is 16:80; the mass of the sodium silicate accounts for 4% of the total mass of the bentonite, carbide slag and sodium silicate; the bentonite, carbide slag and sodium silicate are 100% by weight. The mass ratio of the total mass of the bentonite to the water is 1:0.8; the chemical composition of the bentonite is as follows by mass percentage: CaO: 2.24%, SiO2: 73.33%, Al2O3: 13.55%, Na2O: 4.25%, Fe2O3: 2.26%, MgO: 3.59%, TiO2: 0.12%, K2O: 0.50%, impurities: 0.16%; the chemical composition of the carbide slag is as follows by mass percentage: CaO: 93.65%, SiO2: 2.97%, Al2O3: 0.82%, Na2O: 0.71%, Fe2O3: 0.22%, MgO: 0.15%, TiO2: 0.06%, impurities: 1.42%;
[0132] The heavy metal Cu 2+ A device for preparing a crystalline metal CuO thin film by spontaneous film formation comprises a lower plate and an upper plate which are stacked in sequence; the upper plate is provided with a through hole; the lower plate is provided with a vertical card plate, and the upper plate and the lower plate are fixed together by the vertical card plate; the through hole of the upper plate has a diameter of 5 mm and a depth of 1 mm, the diameter of the through hole is 2 mm larger than the length of the composite mineral particle, and the center distance of the hole is 4 times the diameter of the hole; the length of the vertical card plate is 5 cm, the width is 1 cm, and the height is 5 mm larger than the sum of the thickness of the upper plate and the lower plate;
[0133] After obtaining particles with a crystalline metal CuO film on the outer layer, the acidic heavy metal copper sulfate water sample after the reaction is discharged and recycled, and the upper plate with the crystalline metal CuO film grown is taken out, the crystalline metal CuO film remains on the upper plate, and the particles remain on the lower plate, completing the separation of the crystalline metal CuO film and the particles, and then the crystalline metal CuO film on the upper plate is gently scraped off to make it fall off and collected for recycling, the particles left on the lower plate are collected as by-products, dried in an oven at 105°C for 4 hours, and then recycled, the recycled particles can be recycled as an adsorbent for adsorbing heavy metal ions, and the recycled particles can continue to be recycled as metal mineral resources after being saturated with heavy metal ions, thereby realizing a waste-free, green, and circular economy.
[0134] The heavy metal Cu provided by the present invention 2+ The crystalline CuO thin film prepared by spontaneous film formation is dense, dark black, and has a crystal purity of more than 90%. 2+ Spontaneous film formation has a good effect on the preparation of crystalline metal CuO thin films.
[0135] Example 3
[0136] A heavy metal Cu 2+ The method for preparing a crystalline metal CuO thin film by spontaneous film formation comprises the following steps:
[0137] 1.0 g of composite mineral particles were evenly dispersed in a device for spontaneous film formation to prepare crystalline metal oxide thin films, and the device was placed in a 1 L liquid with an initial pH of 3.2 and heavy metal Cu 2+ In the acidic heavy metal copper sulfate water sample with a concentration of 300 mg / L, the static conditions and the initial water temperature of the water sample were controlled at 30°C. When the outer film color of the composite mineral particles turned blue-green, the water temperature continued to be maintained at 30°C for the first hydration reaction until the outer film color of the composite mineral particles turned black and the reaction was stopped. The initial reaction obtained a colloidal liquid film, and then the heavy metal ion Cu 2+ The synergistic effect of adsorption-precipitation-crystallization self-growth-oxidation is performed to obtain particles having a crystalline metal CuO film on the outer layer; in the particles having a crystalline metal CuO film on the outer layer, there is a distance between the crystalline metal CuO film and the particles;
[0138] The preparation method of the composite mineral particles comprises the following steps:
[0139] The bentonite and carbide slag are dried in an oven at 105°C for 3 hours until the moisture content is less than 10%, and then mixed evenly with sodium carbonate in a mechanical stirrer, and then water is added and mixed for 15 minutes for a second hydration reaction, and then a granulator is used to make particles with a diameter of 2 mm and a length of 3 mm. The granulated particles are covered with plastic cloth, aged at 25°C for 4 hours, and then calcined at 350°C for 1 hour for dehydration condensation, and then naturally cooled to obtain composite mineral particles; the particle size of the bentonite and carbide slag is independently ≤74μm; the mass ratio of the bentonite and carbide slag is 25.5:70; the mass of the sodium carbonate accounts for 4.5% of the total mass of the bentonite, carbide slag and sodium carbonate; the bentonite, carbide slag and carbon are 1.375 μm and 1.675 μm, respectively. The mass ratio of the total mass of sodium phosphate to water is 1:0.8; the chemical composition of the bentonite is as follows by mass percentage: CaO: 2.24%, SiO2: 73.33%, Al2O3: 13.55%, Na2O: 4.25%, Fe2O3: 2.26%, MgO: 3.59%, TiO2: 0.12%, K2O: 0.50%, impurities: 0.16%; the chemical composition of carbide slag is as follows by mass percentage: CaO: 93.65%, SiO2: 2.97%, Al2O3: 0.82%, Na2O: 0.71%, Fe2O3: 0.22%, MgO: 0.15%, TiO2: 0.06%, impurities: 1.42%;
[0140] The heavy metal Cu 2+ A device for preparing a crystalline metal CuO thin film by spontaneous film formation comprises a lower plate and an upper plate which are stacked in sequence; the upper plate is provided with a through hole; the lower plate is provided with a vertical card plate, and the upper plate and the lower plate are fixed together by the vertical card plate; the through hole of the upper plate has a diameter of 5 mm and a depth of 1 mm, the diameter of the through hole is 2 mm larger than the length of the composite mineral particle, and the center distance of the hole is 4 times the diameter of the hole; the length of the vertical card plate is 5 cm, the width is 1 cm, and the height is 5 mm larger than the sum of the thickness of the upper plate and the lower plate;
[0141] After obtaining the mineral particles with a crystalline metal CuO film on the outer layer, the acidic heavy metal copper sulfate water sample after the reaction is discharged and recycled, and the upper plate with the crystalline metal CuO film grown is taken out, the crystalline metal CuO film remains on the upper plate, and the mineral particles remain on the lower plate, completing the separation of the crystalline metal CuO film and the mineral particles, and then the crystalline metal CuO film on the upper plate is gently scraped off to make it fall off and collected for recycling, and the mineral particles left on the lower plate are collected as by-products, naturally dried for 48 hours and then recycled, and the recycled mineral particles can be recycled as an adsorbent for adsorbing heavy metal ions, and the recycled mineral particles can continue to be recycled as metal mineral resources after being saturated with heavy metal ions, thereby realizing a waste-free, green and circular economy.
[0142] The heavy metal Cu provided by the present invention 2+ The crystalline metal CuO film prepared by spontaneous film formation is dark black in color and has a crystal purity of more than 90%. 2+ Spontaneous film formation has a good effect on the preparation of crystalline metal CuO thin films.
[0143] Example 4
[0144] A heavy metal Cu 2+ The method for preparing a crystalline metal CuO thin film by spontaneous film formation comprises the following steps:
[0145] 5.0 g of composite mineral particles were evenly dispersed in a device for spontaneous film formation to prepare crystalline metal oxide thin films, and the device was placed in a 1 L solution with an initial pH of 3.5 and heavy metal Cu 2+ In the acidic heavy metal copper sulfate water sample with a concentration of 680 mg / L, the water sample was controlled to undergo the first hydration reaction at 25°C and static conditions to obtain a colloidal liquid film, and then the heavy metal ion Cu 2+ The synergistic effect of adsorption-precipitation-crystallization self-growth-oxidation is performed to obtain particles having a crystalline metal CuO film on the outer layer; in the particles having a crystalline metal CuO film on the outer layer, there is a distance between the crystalline metal CuO film and the particles;
[0146] The preparation method of the composite mineral particles comprises the following steps:
[0147] The bentonite and carbide slag are dried in an oven at 105°C for 3 hours until the moisture content is less than 10%, and then mixed with sodium silicate in a mechanical stirrer. Water is then added and mixed for 15 minutes for a second hydration reaction. Then, a granulator is used to make particles with a diameter of 2 mm and a length of 3 mm. The particles obtained by granulation are covered with plastic cloth, aged at 25°C for 12 hours, and then calcined at 350°C for 1.2 hours for dehydration condensation, and then naturally cooled to obtain composite mineral particles; the particle sizes of the bentonite and carbide slag are independently ≤74μm; the mass ratio of the bentonite and carbide slag is 36.0:60; the mass of the sodium silicate accounts for 4% of the total mass of the bentonite, carbide slag and sodium silicate; the bentonite, carbide slag and The mass ratio of the total mass of sodium silicate to water is 1:0.7; the chemical composition of the bentonite is as follows by mass percentage: CaO: 2.24%, SiO2: 73.33%, Al2O3: 13.55%, Na2O: 4.25%, Fe2O3: 2.26%, MgO: 3.59%, TiO2: 0.12%, K2O: 0.50%, impurities: 0.16%; the chemical composition of carbide slag is as follows by mass percentage: CaO: 93.65%, SiO2: 2.97%, Al2O3: 0.82%, Na2O: 0.71%, Fe2O3: 0.22%, MgO: 0.15%, TiO2: 0.06%, impurities: 1.42%;
[0148] The heavy metal Cu 2+ A device for preparing a crystalline metal CuO thin film by spontaneous film formation comprises a lower plate and an upper plate which are stacked in sequence; the upper plate is provided with a through hole; the lower plate is provided with a vertical card plate, and the upper plate and the lower plate are fixed together by the vertical card plate; the through hole of the upper plate has a diameter of 5 mm and a depth of 1 mm, the diameter of the through hole is 2 mm larger than the length of the composite mineral particle, and the center distance of the hole is 4 times the diameter of the hole; the length of the vertical card plate is 5 cm, the width is 1 cm, and the height is 5 mm larger than the sum of the thickness of the upper plate and the lower plate;
[0149] After obtaining particles with a crystalline metal CuO film on the outer layer, the acidic heavy metal copper sulfate water sample after the reaction is discharged and recycled, and the upper plate with the crystalline metal CuO film grown is taken out, the crystalline metal CuO film remains on the upper plate, and the particles remain on the lower plate, completing the separation of the crystalline metal CuO film and the particles, and then the crystalline metal CuO film on the upper plate is gently scraped off to make it fall off and collected for recycling, and the particles left on the lower plate are collected as by-products, naturally dried for 48 hours and then recycled, and the recycled particles can be recycled as adsorbents for adsorbing heavy metal ions, and the recycled particles can continue to be recycled as metal mineral resources after being saturated with heavy metal ions, thereby realizing a waste-free, green and circular economy.
[0150] The heavy metal Cu provided by the present invention 2+ The crystalline CuO thin film prepared by spontaneous film formation is dense, dark black, and has a crystal purity of more than 90%. 2+ Spontaneous film formation has a good effect on the preparation of crystalline metal CuO thin films.
[0151] Example 5
[0152] A heavy metal Zn 2+ The method for preparing a crystalline metal ZnO thin film by spontaneous film formation comprises the following steps:
[0153] 1.0 g of composite mineral particles were evenly dispersed in a device for spontaneous film formation to prepare crystalline metal oxide thin films, and the device was placed in a 1 L liquid with an initial pH of 3.0 and heavy metal Zn 2+ In the acidic heavy metal zinc sulfate water sample with a concentration of 300 mg / L, the water sample was controlled to be static at 25°C at the initial stage. When the outer film color of the composite mineral particles turned white, the shaking table speed was 70 r / min for the first hydration reaction until the outer film color of the composite mineral particles turned white and transparent, and the reaction was stopped to obtain a colloidal liquid film. Then, the heavy metal ion Zn 2+ The synergistic effect of adsorption-precipitation-crystallization self-growth-oxidation is performed to obtain particles having a crystalline metal ZnO film on the outer layer; in the particles having a crystalline metal ZnO film on the outer layer, there is a distance between the crystalline metal ZnO film and the particles;
[0154] The preparation method of the composite mineral particles comprises the following steps:
[0155] The bentonite and carbide slag are dried in an oven at 105°C for 3 hours until the moisture content is less than 10%, and then mixed with sodium carbonate in a mechanical stirrer. Water is then added and mixed for 15 minutes for a second hydration reaction. Then, a granulator is used to make particles with a diameter of 2 mm and a length of 3 mm. The particles obtained by granulation are covered with plastic cloth, aged at 20°C for 10 hours, and then calcined at 350°C for 1 hour for dehydration condensation, and then naturally cooled to obtain composite mineral particles; the particle sizes of the bentonite and carbide slag are independently ≤74μm; the mass ratio of the bentonite and carbide slag is 20:75; the mass of the sodium carbonate accounts for 5% of the total mass of the bentonite, carbide slag and sodium carbonate; the bentonite, carbide slag and sodium carbonate are 100% by weight. The mass ratio of the total mass of the bentonite to the water is 1:0.7; the chemical composition of the bentonite is as follows by mass percentage: CaO: 2.24%, SiO2: 73.33%, Al2O3: 13.55%, Na2O: 4.25%, Fe2O3: 2.26%, MgO: 3.59%, TiO2: 0.12%, K2O: 0.50%, impurities: 0.16%; the chemical composition of the carbide slag is as follows by mass percentage: CaO: 93.65%, SiO2: 2.97%, Al2O3: 0.82%, Na2O: 0.71%, Fe2O3: 0.22%, MgO: 0.15%, TiO2: 0.06%, impurities: 1.42%;
[0156] The heavy metal Zn 2+ A device for preparing a crystalline metal ZnO thin film by spontaneous film formation comprises a lower plate and an upper plate which are stacked in sequence; the upper plate is provided with a through hole; the lower plate is provided with a vertical card plate, and the upper plate and the lower plate are fixed together by the vertical card plate; the through hole of the upper plate has a diameter of 5 mm and a depth of 1 mm, the diameter of the through hole is 2 mm larger than the length of the composite mineral particle, and the center distance of the hole is 4 times the diameter of the hole; the length of the vertical card plate is 5 cm, the width is 1 cm, and the height is 5 mm larger than the sum of the thickness of the upper plate and the lower plate;
[0157] After obtaining particles with a crystalline metal ZnO film on the outer layer, the acidic heavy metal copper sulfate water sample after the reaction is discharged and recycled, and the upper plate with the crystalline metal ZnO film grown is taken out, the crystalline metal ZnO film remains on the upper plate, and the particles remain on the lower plate, completing the separation of the crystalline metal ZnO film and the particles, and then the crystalline metal ZnO film on the upper plate is gently scraped off to make it fall off and collected for recycling, the particles left on the lower plate are collected as by-products, dried in an oven at 105°C for 4 hours, and then recycled, the recycled particles can be recycled as an adsorbent for adsorbing heavy metal ions, and the recycled particles can continue to be recycled as metal mineral resources after being saturated with heavy metal ions, thereby realizing a waste-free, green, and circular economy.
[0158] The heavy metal Zn provided by the present invention 2+ The crystalline ZnO thin film prepared by the spontaneous film formation method is dense, white and transparent, and the crystal purity reaches more than 90%. 2+ Spontaneous film formation has good effect in preparing crystalline metal ZnO thin films.
[0159] Comparative Example 1
[0160] The difference from Example 1 is that undried carbide slag is used and the moisture content is controlled at 50-70%. The rest of the contents are consistent with Example 1.
[0161] Compared with Example 1, the use of carbide slag with a high moisture content results in the heat released by the carbide slag in the initial stage not being utilized (because only the CaO and Ca(OH)2 in the dry carbide slag will undergo hydrolysis to generate Ca(OH)2 after encountering water H2O and release a large amount of heat which is beneficial to the hydration reaction), which is not conducive to the hydration reaction with bentonite to form hydrated calcium silicate (CSH) gel, etc.
[0162] Comparative Example 2
[0163] The difference from Example 1 is that bentonite, carbide slag and sodium carbonate are mechanically mixed uniformly to form a mixture A; the mixture A is extruded and crushed to form mixed particles B, and the mixed particles B are directly roasted without aging. The rest of the content is consistent with Example 1.
[0164] Compared with Example 1, the crushing effect can easily cause the mixed particles B to become loose and cracked, affecting the adhesion of the particles and making them unable to be well formed. In addition, the prepared mixed particles B are not aged, the hydration reaction is insufficient, and the hydrated calcium silicate (CSH) gel cannot be well formed, which is not conducive to the adhesion of the particles.
[0165] Comparative Example 3
[0166] The difference from Example 1 is that undried carbide slag is used, and the moisture content is controlled at 50-70%, and bentonite, carbide slag and sodium carbonate are mechanically mixed and uniformly prepared into a mixture A; the mixture A is extruded and crushed to prepare mixed particles B, and the mixed particles B are directly roasted without aging, and the rest of the contents are consistent with Example 1.
[0167] Compared with Example 1, the use of carbide slag with high water content causes the heat released in the initial stage of the carbide slag to be not utilized, which is not conducive to the hydration reaction with bentonite to form calcium silicate hydrate (CSH) gel, etc. At the same time, due to the crushing effect, the mixed particles B become loose and cracked, which affects the particle cohesion and cannot be well formed. In addition, the prepared mixed particles B are not aged, the hydration reaction is insufficient, and the calcium silicate hydrate (CSH) gel, etc. cannot be well formed; since the amount of calcium silicate hydrate (CSH) gel in the composite particles is small, only a small amount of amorphous is formed after dehydration condensation. The tricalcium silicate 3CaO·SiO2 or dicalcium silicate 2CaO·SiO2, when the composite particles after dehydration condensation are used, the hydration reaction of water absorption is not obvious when put into water, the amount of hydrated calcium silicate (CSH) gel generated again is small, and it cannot release heat and expand locally. A spherical colloidal liquid film rich in Ca(OH)2 colloidal structure cannot be formed around the particles, and induced crystallization to form heavy metal basic sulfate crystals cannot occur. A crystalline metal oxide film cannot be formed, but only Cu(OH)2 precipitation is generated in the water sample around the particles.
[0168] Performance Testing
[0169] Figure 3 Schematic diagram of the film structure formed by the spontaneous formation of colloidal liquid film by the hydration reaction of composite mineral particles as the substrate to adsorb heavy metal cations. Figure 3 It can be seen that a spherical colloidal liquid film is generated at a certain distance around the composite mineral particles.
[0170] Figure 4 The composite mineral particles obtained in Example 1 of the present invention spontaneously form a colloidal liquid film and react with the heavy metal Cu in the copper sulfate solution. 2+ The effect diagram of spontaneous film formation of crystalline metal CuO thin film. Figure 5 The composite mineral particles obtained in Example 5 of the present invention spontaneously form a colloidal liquid film and react with the heavy metal Zn in the zinc sulfate solution. 2+ The effect diagram of spontaneous film formation of crystalline metal ZnO thin film. Figure 4 and Figure 5 The colloidal liquid film formed and the heavy metal Cu 2+ and Zn 2+ The spontaneous film formation effect diagram shows that the prepared composite mineral particles can spontaneously form colloidal liquid films in acidic heavy metal sulfate samples, and according to Figure 4 , Figure 5 It can be clearly seen that the colloidal liquid film has a strong 2+ 、Zn 2+ Crystalline metal CuO and ZnO thin films were prepared by spontaneous film formation.
[0171] Figure 6 This is a photo of bentonite, the raw material of the present invention. Figure 7 This is a photo of carbide slag, the raw material of the present invention. Figure 8 This is a photo of the composite mineral particles prepared in Example 1 of the present invention. Fig. 9 The XRD diffraction patterns of bentonite and carbide slag are shown in Table 1. Figure 6 and Figure 7 It can be seen that bentonite and carbide slag are both fine powder particles. Figure 8 It can be seen that the prepared composite mineral particles are uniform in size and not easy to loosen. Fig. 9 It can be seen that bentonite and carbide slag have fewer impurities.
[0172] Fig.10 The composite mineral particles obtained in Example 1 of the present invention are 2+ XRD diffraction pattern of crystalline metal CuO thin film prepared by spontaneous film formation, Fig.11 The composite mineral particles obtained in Example 1 of the present invention are 2+ SEM image of crystalline CuO thin film prepared by spontaneous film formation. Fig.12 The composite mineral particles obtained in Example 1 of the present invention are 2+ EDS image of crystalline CuO thin film prepared by spontaneous film formation. Figures 10-12 It can be seen that the composite mineral particles have a great influence on the heavy metal Cu 2+ The crystalline CuO thin film prepared by spontaneous film formation is mainly composed of hierarchical flower-shaped or prismatic CuO crystals, with a purity of 76.77% of heavy metal copper and a ratio of 45:54 of copper atoms to oxygen atoms, which basically conforms to the theoretical stoichiometric ratio of 1:1. The purity of the mineral phase of the crystalline CuO thin film can reach more than 90%. Fig.12 It can also be seen that except for Cu and O, no other impurities were detected, proving that the sample has good purity.
[0173] Fig.13 The composite mineral particles obtained in Example 2 of the present invention spontaneously form a colloidal liquid film and react with the heavy metal Cu in the copper sulfate solution. 2+ The effect diagram of spontaneous film formation of crystalline metal CuO thin film. Fig.14 The composite mineral particles obtained in Example 3 of the present invention spontaneously form a colloidal liquid film and react with the heavy metal Cu in the copper sulfate solution. 2+ The effect diagram of spontaneous film formation of crystalline metal CuO thin film. Fig.15 The composite mineral particles obtained in Example 4 of the present invention spontaneously form a colloidal liquid film and react with the heavy metal Cu in the copper sulfate solution. 2+ The effect diagram of spontaneous film formation of crystalline metal CuO thin film. Fig.16 The composite mineral particles obtained in Example 4 of the present invention are 2+SEM image of crystalline CuO thin film prepared by spontaneous film formation. Fig.13 , Fig.14 , Fig.15 The colloidal liquid film formed and the heavy metal Cu 2+ The spontaneous film formation effect diagram shows that the prepared composite mineral particles can spontaneously form colloidal liquid films in acidic heavy metal sulfate samples, and according to Fig.13 , Fig.14 , Fig.15 It can be clearly seen that the colloidal liquid film has a strong 2+ A dark black crystalline CuO thin film was prepared by spontaneous film formation. Fig.16 SEM shows that the surface of the crystalline metal CuO film presents a continuous array of wrinkled morphology with obvious texture, smooth and orderly, complete and dense structure, and the crystal purity reaches more than 90%.
[0174] Fig.17 This is a diagram showing the effect of the composite mineral particles prepared in comparative example 3 of the present invention in a copper sulfate solution. Fig.17 It can be seen that the composite mineral particles prepared in Comparative Example 3 cannot form a crystalline metal CuO film, but only generate Cu(OH)2 precipitation in the water sample around the particles.
[0175] The invention provides a method for preparing a crystalline metal oxide film by spontaneous film formation. The crystalline metal oxide film prepared by controlling the dosage ratio of composite mineral particles and acidic heavy metal sulfate water sample, controlling the pH value of the water sample, the concentration of heavy metal ions, and the hydration reaction conditions is dense and has a crystal purity of more than 90%. The heavy metal ions have good effects in spontaneous film formation for preparing the crystalline metal oxide film. The method for preparing a crystalline metal oxide film by spontaneous film formation provided by the invention can realize simple experimental device, low raw material cost, no need for substrate or base sheet, spontaneous film formation, and the obtained metal oxide film has the advantages of high crystallinity, controllable grain size, dense film, good performance, short process flow, safe and convenient operation, energy saving, etc., and can realize concepts such as turning alkaline industrial solid waste carbide slag into treasure, waste resource utilization, clean production, circular economy, and low-carbon environmental protection green development.
[0176] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a crystalline metal oxide thin film by spontaneous film formation, characterized in that: The following steps are involved: The composite mineral particles and the acidic heavy metal sulfate water sample are mixed to perform a first hydration reaction, during which the composite mineral particles generate a hydrated gel liquid film containing calcium hydroxide, the hydrated gel liquid film adsorbs heavy metal ions and spontaneously generates a film containing metal hydroxide, the metal hydroxide decomposes to generate metal oxides through oxidation, and thus mineral particles having a crystalline metal oxide film on the outer layer are obtained; Separating the crystalline metal oxide film from the mineral particles having the crystalline metal oxide film on the outer layer to obtain the crystalline metal oxide film; The method for preparing the composite mineral particles comprises the following steps: Mixing bentonite, carbide slag, alkaline activator and water to carry out a second hydration reaction to obtain a second hydration reaction product; The second hydration reaction product is sequentially granulated, aged and dehydrated to obtain composite mineral particles; The particle sizes of the bentonite and carbide slag are independently ≤74 μm.
2. The method according to claim 1, characterized in that The concentration of heavy metal ions in the acidic heavy metal sulfate water sample is 200-1000 mg / L, and the pH value is 3-6; the ratio of the mass of the composite mineral particles to the volume of the acidic heavy metal sulfate water sample is (1-10) g:1L.
3. The method according to claim 1 or 2, characterized in that: When the heavy metal ion concentration in the acidic heavy metal sulfate water sample is 500-1000 mg / L, the temperature of the first hydration reaction is 10-30° C., and the first hydration reaction is performed under static conditions; Or when the heavy metal ion concentration in the acidic heavy metal sulfate water sample is 300-500 mg / L, the initial temperature of the first hydration reaction is 10-30° C., when the color of the outer film of the composite mineral particles changes, the temperature is increased to 30-50° C., and the reaction is stopped when the color of the outer film of the composite mineral particles remains unchanged, and the first hydration reaction is carried out under static conditions; Or when the heavy metal ion concentration in the acidic heavy metal sulfate water sample is 200-500 mg / L, the temperature of the first hydration reaction is 10-30°C, the first hydration reaction is initially carried out under static conditions, when the color of the outer film of the composite mineral particles changes, the reaction is carried out under stirring conditions, and the reaction is stopped when the color of the outer film of the composite mineral particles remains unchanged; the stirring speed is 30-100 r / min.
4. The method according to claim 1, characterized in that: The alkaline activator includes sodium carbonate and / or sodium silicate.
5. The method according to claim 1 or 4, characterized in that: The mass ratio of the bentonite to the carbide slag is (13-36.5):(60-80); The mass of the alkaline activator accounts for 3.5-7% of the total mass of the bentonite, carbide slag and the alkaline activator.
6. The method according to claim 1, characterized in that The chemical composition of the bentonite includes, by mass percentage, SiO2: 65-80%, Al2O3: 11-17%, Na2O: 3.0-6.0%, CaO: 2.0-3.5%, MgO: 2.0-5.0%, Fe2O3: 1.6-4.0%, TiO2: 0.04-0.20%, K2O: 0.1-1.2%, and impurities: 0.10-2.16%; The chemical composition of the carbide slag includes: CaO: 86.7-94.5%, SiO2: 2.0-6.5%, Al2O3: 0.5-3.0%, Na2O: 0.5-2.5%, Fe2O3: 0.2-1.5%, MgO: 0.10-0.22%, TiO2: 0.01-0.08%, and impurities: 1.0-1.72%.
7. The method according to claim 1, characterized in that The mass ratio of the total mass of the bentonite, carbide slag and alkaline activator to water is 1:(0.6-0.9).
8. The method according to claim 1, characterized in that The aging temperature is 10-35° C. and the aging time is 2-12 hours.
9. The method according to claim 1, characterized in that: The dehydration condensation comprises: drying under natural conditions for 24 to 48 hours; Or the dehydration condensation temperature is 150-450° C., and the time is 0.6-1.5 h.
10. A device for use in the method according to any one of claims 1 to 9, characterized in that: It comprises a lower plate and an upper plate which are stacked in sequence; the upper plate is provided with a through hole which is perpendicular to the lower plate.